Z metodologicznych doświadczeń badań nad odbiorem współczesnej prozy polskiej = Methodological Experiences from Studies on Polish-contemporary-prose perception - Marzec, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
During studies on Polish-contemporary-prose perception in a Secondary School various difficulties and methodological complications were brought to light. Among the most important one must mention the lack of tradition of such studies, the need for interdisciplinary handling, the multiple and manifold theories of the structure of a work and of the process of its cognition and the more the necessity for instrumental handling of notions, which theoreticians of literature and psychologists left as debatable. One must take into consideration the fact, that the quality of perception of a work of art depends on several outside conditions, which influence the construction of the investigating instruments.
Keywords: metodologia; proza polska; badania